2020
DOI: 10.1253/circj.cj-19-0826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Box Isolation on Rotors and Multiple Wavelets in Persistent Atrial Fibrillation

Abstract: Background: Additional benefits of posterior left atrial (LA) box isolation (BOXI) over pulmonary vein isolation (PVI) in persistent atrial fibrillation (perAF) have been reported, but the mechanism is still unclear. We evaluated the effects of BOXI on rotors and multiple wavelets in the whole LA. Methods and Results: Twenty patients with perAF (including 12 cases of longstanding perAF) underwent PVI. Real-time phase mapping (ExTRa Mapping) was performed in the whole LA during AF. Subsequently, BOXI was added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This is consistent with the embryologic origin of the SVC from the sinus venous (as is the sinoatrial node), which explains the arrhythmogenic properties of this structure. LAPW is also reported to be a frequent non‐PV site, and the additional benefit of its isolation over PVI in patients with PEAF has been reported in a previous study 16 . This structure mainly includes the PV antrum and is embryologically derived from the primordial PV 17,18 .…”
Section: Discussionmentioning
confidence: 73%
“…This is consistent with the embryologic origin of the SVC from the sinus venous (as is the sinoatrial node), which explains the arrhythmogenic properties of this structure. LAPW is also reported to be a frequent non‐PV site, and the additional benefit of its isolation over PVI in patients with PEAF has been reported in a previous study 16 . This structure mainly includes the PV antrum and is embryologically derived from the primordial PV 17,18 .…”
Section: Discussionmentioning
confidence: 73%
“…A previous study found that PVI plus the isolation of the posterior wall facilitated AF termination, suggesting great contribution of the posterior wall in AF termination ( 27 ). Phase mapping of the LA rotor and wavelets in persistent AF indicated that the isolation of the posterior wall not only reduced the critical mass for maintenance of AF within the posterior wall but also decreased the rotors and multiple wavelets in the other regions ( 28 ). Thus, the LVZ of the posterior wall might play a more important role compared with the anterior wall in the advanced stage of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BOXI in addition to the PVI results in a better outcome than a PVI alone or PVI plus a roof line ablation in patients with persistent AF 4‐12 . The BOXI can capture the triggers, rotors, and low‐voltage areas in the posterior LA, 5 facilitate AF termination and its noninducibility, 5 and decrease the rotors and multiple wavelets on the anterior wall, inferior wall, and LA appendage 20 …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] The BOXI can capture the triggers, rotors, and low-voltage areas in the posterior LA, 5 facilitate AF termination and its noninducibility, 5 and decrease the rotors and multiple wavelets on the anterior wall, inferior wall, and LA appendage. 20…”
Section: Beneficial Effects Of the Boxi In Persistent Afmentioning
confidence: 99%